The Application of Good Work Motivation to Increase Employee Productivity Salam Indonesia Travel - Huwaidaul Azkiya; Setyo Riyanto (Journal of Social Science, 2020)
The main reason for compiling this journal is to find out the application of good work motivation to increase employee productivity salam Indonesia travel. The research method used in this study is qualitative descriptive. Information collection procedures utilized in this study are the strategy of perception, interviews, and documentation considers. Information examination procedures in this study include the steps of data reduction, data display, and drawing conclusions. The result of the study found that the Motivation must be applied because it is one of the most important components in supporting the efficiency of worker productivity, without motivation, an employee will lose enthusiasm for work. The leader of Salam Indonesia Travel in increasing employee motivation using methods that are appropriate to the situation of the company and employees. Because every employee has different behaviors and actions at work, so the provision of motivation must be different as well. Highly motivated individuals mean that these people have a compelling reason to get the job done as the company wants. Conversely, when individuals have low motivation, they cannot work well together to achieve the desired performance efficiency of the company.